2013
DOI: 10.1021/cs4009495
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Homogeneous Brønsted Acid Catalyzed Fructose Dehydration and 5-Hydroxymethyl Furfural Rehydration: A Combined Experimental and Computational Study

Abstract: We perform the first extensive experimental kinetic studies of fructose dehydration and 5-hydroxymethyl furfural (HMF) rehydration at low temperatures over a wide range of conditions (T ∼ 70–150 °C; pH values 0.7–1.6 and initial concentrations of fructose (5–20%w/v) and HMF (2.5–10%w/v)). Guided from insights from our first-principles calculations, we perform kinetic isotope effect (KIE) experiments of labeled fructose to validate the rate-limiting step. Subsequently, we develop the first skeleton model for fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 42 publications
(108 reference statements)
7
139
3
Order By: Relevance
“…However, this can be compensated by applying a higher temperature. This might be even beneficial for achieving high maximal HMF yields, as it is reported that the selectivity of HMF formation increases with increasing temperature …”
Section: Discussionmentioning
confidence: 99%
“…However, this can be compensated by applying a higher temperature. This might be even beneficial for achieving high maximal HMF yields, as it is reported that the selectivity of HMF formation increases with increasing temperature …”
Section: Discussionmentioning
confidence: 99%
“…[26] At 130 o C, the FA/LA yield is higher but humins remain the dominant product. [26] At 130 o C, the FA/LA yield is higher but humins remain the dominant product.…”
Section: Hmf Degradation In Crcl3mentioning
confidence: 99%
“…[14] Parameter estimation involves fitting the transient profiles of glucose, mannose, fructose, HMF, and LA using the fminunc minimization routine in Matlab R2013a. [26] Results and discussion [26] Results and discussion…”
Section: Reaction Network and Kinetic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, substantial formation of high molecular weight compounds, that is, aggregates of sugars and humins (polydispersed heterogeneous carbonaceous materials), occurred. Mechanistic aspects of humins formation have recently been addressed [20][21][22][23][24][25]. Their formation mechanism has been related to polycondensation reactions giving a network of furan rings linked by ether or acetal bonds [20].…”
Section: Introductionmentioning
confidence: 99%